IMPLEMENTASI THEORY OF PLANNED BEHAVIOR DALAM MENENTUKAN CONTINUOUS USAGE PADA GAMERS MUDA - Stiven, (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study is motivated by the rapid growth of the online gaming industry and the pivotal role of Microtransaction models in sustaining young players’ engagement. It aims to identify the determinants of continuous usage behavior among Indonesian gamers aged 17–24 by extending the Theory of Planned Behavior with Trust and Financial Inclusion. A cross-sectional quantitative design was employed, surveying 144 respondents via an online questionnaire, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Perceived Behavioral Control (β = 0.324; p < 0.001) and Intention (β = 0.557; p < 0.001) significantly predict sustained engagement, whereas Attitude, Subjective Norm, Financial Inclusion, and Microtransaction propensity show no significant effects. It is concluded that enhancing purchase-control mechanisms and transaction security is essential for maintaining long-term usage, and future research should adopt longitudinal designs with more diverse samples.